Chemical indexes calculated for 8,11,13-trienabietane diterpenoids isolated from Swartzia species - Magalhães, Aderbal Farias; Tozzi, Ana Maria Goulart de Azevedo; Santos, Celira Caparica; Magalhães, Eva Gonçalves (Eclética Química, 2010)
The disparity found in the molecular structures of compounds isolated from nine plants of the Swartzia genus indicates that the Swartzia species that furnished cassane diterpenoids and triterpenoidal saponins are more recent, since these metabolites have adopted the mevalonic acid route of formation, abandoning the shikimic acid/acetate route that produces the isoflavonoids found in the remaining species. Chemical indexes calculated from the molecular structure diversities of sixteen 8,11,13-trien-abietane diterpenoids isolated from Swartzia langsdorffii and S. arborescens indicate that S. arborescens is more recent than S. langsdorffii. The results suggest a more evolved position in Swartzia species of the section Possira.